Combined effect of nisin and high hydrostatic pressure on destruction of Listeria innocua and Escherichia coli in liquid whole egg - Ponce, E; Pla, R; Sendra, E; Guamis, B; Mor-Mur, M (International journal of food microbiology, 1998)
High hydrostatic pressure inactivation of Escherichia coli and Listeria innocua inoculated in liquid whole egg was improved significantly ( P<0.05) with nisin addition at concentrations of 1.25 and 5 mg/l. A reduction of almost 5 log 10 units in E. coli counts and more than 6 log 10 units for L. innocua was obtained at 450 MPa and 5 mg/l of nisin. For this treatment, the two microorganisms were not detectable after 1 month of storage at 4°C. The amount of nisin added did not affect E. coli inactivation at 300 MPa. For L. innocua, 5 mg/l of nisin was more effective than 1.25 mg/l. Nisin showed no effect when samples were stored at 20°C after pressurization, except for samples with L. innocua containing 5 mg/l of nisin and treated with 450 M Pa.